Pengaruh Emosi Negatif dalam Pemilihan Alternatif Investasi Modal: Perbandingan Keputusan Individu dan Kelompok (Studi Eksperimen pada PTS di Surabaya) - Izza Ashsifa; Syaiful Ali (The Indonesian Journal of Accounting Research, 2013)
One kind of managerial decision that affect organization's viability is capital investment decision. This decision needs long-term commitment from organization resources. Traditionally, managers choose capital investment project which give the highest expected financial return. This research will be conducted for two purposes. First, to test the effect of negative emotions (as one kind of non-financial factors) in capital investment decisions, and second, to test the effect of group decision in controlling the negative emotions' effect. A 2x2 mixed-subjects experimental design will be conducted to test Faculty of Economics' undergraduate students in randomly assignment. Between-subject factor is cases with and without emotional trigger events, while within-subjects factor is individual and group judgment task. Analyzed data using non-parametric statistical tests supported both hypotheses. This result consistent with prior research that suggests decision makers should consider both financial data and affect reactions when evaluating investment alternatives. Furthermore, management should also consider the effectiveness of group decisions.